Composition for non-aqueous secondary battery functional layer, non-aqueous secondary battery functional layer, non-aqueous secondary battery component, and non-aqueous secondary battery

By optimizing the ratio of organic particles and water-soluble polymers in the functional layer composition for non-aqueous secondary batteries, the stability of the functional layer composition in a long-term storage and high-temperature environment is solved, and the heat shrinkage resistance is achieved and improve security.

CN111095604BActive Publication Date: 2024-12-31ZEON CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201880060042.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-09-28
Filing Date
2018-09-18
Publication Date
2024-12-31
Estimated Expiration
2038-09-18

AI Technical Summary

Technical Problem

The composition for the functional layer of the existing non-aqueous secondary battery is prone to settle during long-term storage, resulting in a decrease in the stability of the slurry and a short circuit in a high-temperature environment, affecting the safety and performance of the battery.

Method used

The functional layer composition containing organic particles, water-soluble polymer and water is used to ensure that the organic particles contain multifunctional monomer units in a ratio of 20% by mass or more and 95% by mass or less, and the water-soluble polymer is 15% by mass or more. Moreover, the ratio of 100 mass % or less contains hydroxyl-containing structural units, which optimizes the stability of the slurry and heat shrinkage resistance.

Benefits of technology

The slurry stability and heat shrinkage resistance of the functional layer are significantly improved, the safety and circulation characteristics of the battery are ensured, short circuits are avoided, and the performance of the battery in high temperature environment is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002412773430000361
    Figure BDA0002412773430000361
  • Figure BDA0002412773430000371
    Figure BDA0002412773430000371
Patent Text Reader

Abstract

The present invention aims to provide a composition for a non-aqueous secondary battery functional layer, which has excellent slurry stability and can form a functional layer that fully ensures heat shrinkage resistance. The composition for a non-aqueous secondary battery functional layer of the present invention comprises organic particles, a water-soluble polymer and water, wherein the organic particles contain a multifunctional monomer unit at a ratio of 20% by mass or more and 95% by mass or less, and the water-soluble polymer contains a hydroxyl-containing structural unit at a ratio of 15% by mass or more and 100% by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for a non-aqueous secondary battery functional layer, a non-aqueous secondary battery functional layer, a non-aqueous secondary battery member and a non-aqueous secondary battery. Background Art

[0002] Non-aqueous secondary batteries such as lithium-ion batteries (hereinafter sometimes simply referred to as “secondary batteries”) are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are therefore used in a wide range of applications.

[0003] Here, the secondary battery generally has an electrode (positive electrode, negative electrode) and a non-aqueous secondary battery component (hereinafter, sometimes referred to as "battery component") such as a separator that separates the positive electrode and the negative electrode to prevent a short circuit between the positive electrode and the negative electrode. In addition, a porous film layer for improving heat resistance and strength, an adhesive layer for improving the adhesion between battery components, etc. are sometimes provided on the surface of the electrode and / or the separator (hereinafter, these are sometimes collectively referred to as "functional layer"). Specifically, an electrode substrate is formed by providing an electrode composite material layer on a current collector and a functional layer is further formed thereon, and a separator formed by forming a functional layer on a separator substrate is used as a battery component.

[0004] Moreover, the functional layer can be formed by, for example, the following method: applying a slurry-like non-aqueous secondary battery functional layer composition (hereinafter sometimes referred to as the "functional layer composition") containing non-conductive particles such as organic particles and a dispersion medium such as water on the surface of a substrate such as an electrode substrate or a separator substrate, and drying the functional layer composition on the substrate (see, for example, Patent Document 1).

[0005] In Patent Document 1, a composition containing a water-soluble polymer, a water-insoluble polymer, and an aqueous medium and having a spinnability of 60 to 85% as measured by a prescribed method is used to prepare a protective film disposed between a positive electrode and a negative electrode of an electrical storage device. Furthermore, according to Patent Document 1, by using the above composition to prepare a protective film, the charge and discharge characteristics of the electrical storage device can be improved.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: Japanese Patent No. 6083525. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, when the above-mentioned conventional functional layer composition is stored for a long time, components such as organic particles dispersed in the functional layer composition may precipitate (that is, the slurry stability may be impaired).

[0011] In addition, in recent years, there is a demand for further high performance of secondary batteries. Specifically, for secondary batteries using battery components with functional layers, it is required to suppress the thermal shrinkage of the functional layers (i.e., improve the heat shrinkage resistance), thereby fully suppressing the short circuit between the positive and negative electrodes in a high temperature environment, and further ensuring the safety of the secondary battery.

[0012] Therefore, an object of the present invention is to provide a non-aqueous secondary battery functional layer composition which is excellent in slurry stability and can form a functional layer having sufficiently ensured heat shrinkage resistance.

[0013] Another object of the present invention is to provide a nonaqueous secondary battery functional layer having excellent heat shrinkage resistance, a nonaqueous secondary battery member having the functional layer, and a nonaqueous secondary battery having the battery member.

[0014] Solutions for solving problems

[0015] The present inventors have conducted intensive research to solve the above problems. The present inventors have found that a composition for a functional layer comprising organic particles, a water-soluble polymer and water, wherein the organic particles contain multifunctional monomer units at a predetermined ratio and the water-soluble polymer contains hydroxyl-containing structural units at a predetermined ratio, has excellent slurry stability, and that a functional layer having excellent heat shrinkage resistance can be formed by using the composition for a functional layer, thereby completing the present invention.

[0016] That is, the present invention aims to solve the above-mentioned problems advantageously, and the composition for the functional layer of the non-aqueous secondary battery of the present invention is characterized in that it comprises organic particles, water-soluble polymers and water, the organic particles comprise multifunctional monomer units at a ratio of 20% by mass or more and 95% by mass or less, and the water-soluble polymer comprises hydroxyl-containing structural units at a ratio of 15% by mass or more and 100% by mass or less. The composition for the functional layer comprising organic particles, water-soluble polymers and water, the organic particles comprise multifunctional monomer units at a ratio within the above-mentioned range, and the water-soluble polymer comprises hydroxyl-containing structural units at a ratio within the above-mentioned range, has excellent slurry stability, and if the composition for the functional layer is used, a functional layer with excellent heat shrinkage resistance can be formed.

[0017] In the present invention, the term "containing monomer units" for components such as polymers and organic particles formed from polymers means that "a polymer obtained using the monomer contains a structural unit (repeating unit) derived from the monomer". Here, the "content ratio of the structural unit" and "content ratio of the monomer unit" in the polymer can be expressed as 1 H-NMR and 13 C-NMR or other nuclear magnetic resonance (NMR) method.

[0018] In the present invention, the polymer being "water-soluble" means that when 0.5 g of the polymer is dissolved in 100 g of water at 25°C, the insoluble content is less than 0.5% by mass.

[0019] Here, in the non-aqueous secondary battery functional layer composition of the present invention, the water-soluble polymer is preferably nonionic. When a nonionic water-soluble polymer is used, the slurry stability of the functional layer composition can be further improved.

[0020] In the present invention, the water-soluble polymer being "nonionic" means that, when all repeating units of the water-soluble polymer are 100% by mass, the content ratio of the nonionic repeating units is 99% by mass or more and 100% by mass or less.

[0021] Moreover, in the composition for the functional layer of the non-aqueous secondary battery of the present invention, the saponification degree of the water-soluble polymer is preferably 80 mol% or more and 100 mol% or less. If a water-soluble polymer having a saponification degree within the above range is used, it is possible to suppress the generation of stripes and uneven coating when the functional layer is formed by coating the functional layer composition on the substrate (i.e., the coating stability of the functional layer composition can be improved).

[0022] In the present invention, the "saponification degree" of the water-soluble polymer can be measured using the method described in Examples of the present specification.

[0023] Furthermore, in the composition for the non-aqueous secondary battery functional layer of the present invention, the weight average molecular weight of the water-soluble polymer is preferably greater than 10000 and less than 300000. If a water-soluble polymer having a weight average molecular weight within the above range is used, the coating stability of the composition for the functional layer can be improved, and the heat shrinkage resistance of the functional layer can be further improved.

[0024] In the present invention, the "weight average molecular weight" of the water-soluble polymer can be measured using the method described in Examples of the present specification.

[0025] Here, in the composition for a non-aqueous secondary battery functional layer of the present invention, the polyfunctional monomer unit is preferably a polyfunctional ethylenically unsaturated monomer unit. When organic particles containing polyfunctional ethylenically unsaturated monomer units are used, the heat shrinkage resistance of the functional layer can be further improved.

[0026] In the nonaqueous secondary battery functional layer composition of the present invention, the organic particles preferably have a glass transition temperature of 100° C. or higher. When organic particles having a glass transition temperature of the above value are used, the heat shrinkage resistance of the functional layer can be further improved.

[0027] In the present invention, the "glass transition temperature" of the organic particles can be measured using the method described in Examples of the present specification.

[0028] Furthermore, for the composition for the non-aqueous secondary battery functional layer of the present invention, the volume average particle size of the organic particles is preferably 50 nm or more and 500 nm or less. If organic particles with a volume average particle size within the above range are used, the coating stability of the composition for the functional layer can be improved, and the heat shrinkage resistance of the functional layer can be further improved. In addition, the amount of water brought into the secondary battery from the organic particles can be reduced, and the cycle characteristics of the secondary battery can be improved.

[0029] In addition, the present invention aims to advantageously solve the above-mentioned problems, and the non-aqueous secondary battery functional layer of the present invention is characterized in that it is formed using any of the above-mentioned non-aqueous secondary battery functional layer compositions. The functional layer obtained by using any of the above-mentioned functional layer compositions has excellent heat shrinkage resistance.

[0030] Furthermore, the nonaqueous secondary battery component having the nonaqueous secondary battery functional layer of the present invention has excellent resistance to heat shrinkage, and by using the battery component, a secondary battery can be obtained which fully ensures safety and can exhibit good battery characteristics such as cycle characteristics.

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide a non-aqueous secondary battery functional layer composition which is excellent in slurry stability and can form a functional layer having sufficiently ensured heat shrinkage resistance.

[0033] Furthermore, according to the present invention, it is possible to provide a nonaqueous secondary battery functional layer having excellent heat shrinkage resistance, a nonaqueous secondary battery member having the functional layer, and a nonaqueous secondary battery having the battery member. DETAILED DESCRIPTION

[0034] Hereinafter, embodiments of the present invention will be described in detail.

[0035] Here, the composition for the non-aqueous secondary battery functional layer of the present invention can be used as a material for forming the non-aqueous secondary battery functional layer of the present invention. Moreover, the non-aqueous secondary battery functional layer of the present invention is formed using the composition for the non-aqueous secondary battery functional layer of the present invention, constituting, for example, a part of a separator or an electrode. In addition, the non-aqueous secondary battery component of the present invention has the non-aqueous secondary battery functional layer of the present invention. Furthermore, the non-aqueous secondary battery of the present invention has at least the non-aqueous secondary battery component of the present invention.

[0036] (Composition for non-aqueous secondary battery functional layer)

[0037] The functional layer composition of the present invention is a slurry-like composition containing organic particles, a water-soluble polymer, water as a dispersion medium, and optionally containing a binder, inorganic particles and other components. In addition, in the functional layer composition of the present invention, in addition to water, an organic solvent can also be included as a dispersion medium.

[0038] Here, the organic particles contained in the functional layer composition of the present invention contain a polyfunctional monomer unit at a ratio of 20 mass % or more and 95 mass % or less. In addition, the water-soluble polymer contained in the functional layer composition of the present invention contains a hydroxyl-containing structural unit at a ratio of 15 mass % or more and 100 mass % or less.

[0039] Moreover, the functional layer composition of the present invention contains organic particles and a water-soluble polymer, wherein the organic particles contain a multifunctional monomer unit at a ratio of 20 mass % to 95 mass %, and the water-soluble polymer contains a hydroxyl-containing structural unit at a ratio of 15 mass % to 100 mass %. Therefore, the slurry has excellent stability and can impart excellent heat shrinkage resistance to the functional layer obtained using the functional layer composition.

[0040] <Organic particles>

[0041] The organic particles are particles composed of a water-insoluble polymer and are a component that can mainly improve the heat shrinkage resistance, strength, etc. of the functional layer.

[0042] <<Composition>>

[0043] Here, the organic particles contain 20% to 95% by mass of the polyfunctional monomer unit as described above, and contain 5% to 80% by mass of repeating units other than the polyfunctional monomer unit (other repeating units).

[0044] [Multifunctional monomer unit]

[0045] In the present invention, the multifunctional monomer that can form the multifunctional monomer unit is not particularly limited, and a monomer having two or more groups or structures that can form a crosslinked structure by polymerization per molecule can be used. Here, as examples of multifunctional monomers, there can be cited: monomers having one ethylenically unsaturated bond and one or more heat-crosslinkable crosslinking groups per molecule (thermal crosslinking group-containing monomers); monomers having two or more ethylenically unsaturated bonds per molecule (multifunctional ethylenically unsaturated monomers).

[0046] ―Monomers containing thermally crosslinkable groups―

[0047] Examples of heat-crosslinkable crosslinkable groups include epoxy groups, N-methylolamide groups, oxetane groups, oxazoline groups, and combinations thereof. Among these, epoxy groups are more preferred because crosslinking and crosslinking density can be easily adjusted.

[0048] Examples of monomers having an epoxy group as a heat-crosslinkable crosslinkable group and having an ethylenically unsaturated bond include unsaturated glycidyl ethers such as vinyl glycidyl ether, allyl glycidyl ether, butenyl glycidyl ether, and o-allylphenyl glycidyl ether; monoepoxides of dienes or polyenes such as butadiene monoepoxide, chloroprene monoepoxide, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexene, and 1,2-epoxy-5,9-cyclododecadiene; substances; alkenyl epoxides such as 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, and 1,2-epoxy-9-decene; and glycidyl esters of unsaturated carboxylic acids such as glycidyl acrylate, glycidyl methacrylate, glycidyl crotonate, glycidyl-4-heptanoate, glycidyl sorbate, glycidyl linoleate, glycidyl-4-methyl-3-pentanoate, glycidyl ester of 3-cyclohexenoic acid, and glycidyl ester of 4-methyl-3-cyclohexenoic acid.

[0049] Examples of the monomer having an N-methylolamide group as a heat-crosslinkable crosslinkable group and having an ethylenically unsaturated bond include (meth)acrylamide having a methylol group such as N-methylol (meth)acrylamide.

[0050] In the present invention, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0051] Furthermore, examples of monomers having an oxetane group as a heat-crosslinkable crosslinkable group and having an ethylenically unsaturated bond include 3-((meth)acryloyloxymethyl)oxetane, 3-((meth)acryloyloxymethyl)-2-trifluoromethyloxetane, 3-((meth)acryloyloxymethyl)-2-phenyloxetane, 2-((meth)acryloyloxymethyl)oxetane and 2-((meth)acryloyloxymethyl)-4-trifluoromethyloxetane.

[0052] In addition, in the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.

[0053] In addition, examples of monomers having an oxazoline group as a heat-crosslinkable crosslinkable group and having an ethylenically unsaturated bond include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline and 2-isopropenyl-5-ethyl-2-oxazoline.

[0054] ―Multifunctional ethylenically unsaturated monomer―

[0055] Examples of the polyfunctional ethylenically unsaturated monomer include polyfunctional (meth)acrylate monomers such as allyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate;

[0056] Multifunctional aromatic vinyl monomers such as divinylbenzene and diisopropenylbenzene;

[0057] Dipropylene glycol diallyl ether, polyethylene glycol diallyl ether, tripropylene glycol divinyl ether, hydroquinone diallyl ether, tetraallyloxyethane, trimethylolpropane-diallyl ether, allyl or vinyl ethers of polyfunctional alcohols other than the above, triallylamine, methylenebisacrylamide, and the like.

[0058] In addition, in this specification, "(meth)acrylate" means acrylate and / or methacrylate.

[0059] These multifunctional monomers can be used alone or in combination of two or more. Among these, from the viewpoint of further improving the heat shrinkage resistance of the functional layer, preferred multifunctional ethylenically unsaturated monomers, more preferably multifunctional (meth)acrylate monomers, further preferably ethylene glycol dimethacrylate and trimethylolpropane-trimethacrylate.

[0060] Moreover, when all repeating units of the polymer constituting the organic particles are 100% by mass, the content ratio of the multifunctional monomer unit in the organic particles needs to be more than 20% by mass and less than 95% by mass, preferably more than 25% by mass, more preferably more than 30% by mass, further preferably more than 50% by mass, preferably less than 90% by mass. When the ratio of the multifunctional monomer unit in the organic particles is less than 20% by mass, the hardness of the organic particles is reduced, and the heat shrinkage resistance of the functional layer is impaired. On the other hand, when the ratio of the multifunctional ethylenically unsaturated monomer unit in the organic particles exceeds 95% by mass, the polymerization stability during the preparation of the organic particles is reduced, resulting in an increase in microparticles and impaired cycle characteristics of the secondary battery.

[0061] [Other repeating units]

[0062] Although it does not specifically limit as another repeating unit contained in an organic particle, a monofunctional (meth)acrylate monomer unit and an acidic group-containing monomer unit are mentioned.

[0063] ―Monofunctional (meth)acrylate monomer unit―

[0064] Examples of the (meth)acrylate monomer that can form the monofunctional (meth)acrylate monomer unit include alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate.

[0065] These can be used alone or in combination of two or more. Among these, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate are preferred, and n-butyl acrylate is more preferred.

[0066] ―Monomer units containing acidic groups―

[0067] Examples of the acidic group-containing monomer that can form the acidic group-containing monomer unit include a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer.

[0068] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and derivatives thereof, dicarboxylic acids and anhydrides thereof, and derivatives thereof.

[0069] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.

[0070] Examples of the monocarboxylic acid derivative include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.

[0071] Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid.

[0072] Examples of the dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.

[0073] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.

[0074] Furthermore, as the carboxylic acid group-containing monomer, an acid anhydride that generates a carboxylic acid group by hydrolysis can also be used.

[0075] Examples of the sulfonic acid group-containing monomer include styrenesulfonic acid, vinylsulfonic acid (ethylenesulfonic acid), methylvinylsulfonic acid, (meth)allylsulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.

[0076] In addition, in the present invention, "(meth)allyl group" means an allyl group and / or a methallyl group.

[0077] Furthermore, examples of the phosphoric acid group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.

[0078] In addition, in the present invention, "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group.

[0079] The above acidic group-containing monomers can be used alone or in combination of two or more. Among these acidic group-containing monomers, carboxyl group-containing monomers are preferred, and acrylic acid and methacrylic acid are more preferred.

[0080] Moreover, when all repeating units constituting the polymer of the organic particles are 100% by mass, the content ratio of other repeating units in the organic particles needs to be 5% by mass or more and 80% by mass or less, preferably 10% by mass or more, preferably 70% by mass or less. When the proportion of other repeating units in the organic particles is less than 5% by mass, the polymerization stability during the preparation of the organic particles is reduced, thereby increasing the particles and impairing the cycle characteristics of the secondary battery. On the other hand, when the proportion of other repeating units in the organic particles exceeds 80% by mass, the hardness of the organic particles is reduced and the heat shrinkage resistance of the functional layer is impaired.

[0081] <<Preparation method>>

[0082] The organic particles can be produced by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. In this case, the content ratio of each monomer in the monomer composition can be determined according to the content ratio of each repeating unit in the organic particles.

[0083] Moreover, the polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization can be used. In addition, as the polymerization reaction, any reaction such as ionic polymerization, free radical polymerization, living free radical polymerization can be used. During polymerization, seed particles can be used to carry out seed polymerization. The polymerization conditions can be appropriately adjusted according to the polymerization method, etc.

[0084] Furthermore, known additives such as an emulsifier, a polymerization initiator, and a chain transfer agent may be used in the polymerization, and the amounts thereof used are also amounts generally used.

[0085] <<Volume Average Particle Size>>

[0086] The volume average particle size of the organic particles obtained in the above manner is preferably 50 nm or more, more preferably 100 nm or more, preferably 500 nm or less, and more preferably 400 nm or less. If the volume average particle size of the organic particles is 50 nm or more, the specific surface area of ​​the organic particles can be reduced, thereby reducing the amount of water brought into the secondary battery from the organic particles and improving the cycle characteristics of the secondary battery. On the other hand, if the volume average particle size of the organic particles is 500 nm or less, the coating stability of the functional layer composition can be improved, and the functional layer can be densified to further improve the heat shrinkage resistance of the functional layer.

[0087] The volume average particle size of the organic particles can be adjusted by changing the type and amount of the polymerization initiator, chain transfer agent, and / or emulsifier used when preparing the organic particles.

[0088] <<Glass Transition Temperature>>

[0089] In addition, the glass transition temperature of the organic particles obtained in the above manner is preferably 100° C. or higher, more preferably 110° C. or higher, more preferably 150° C. or higher, and further preferably 200° C. or higher. If the glass transition temperature of the organic particles is 100° C. or higher, the heat shrinkage resistance of the functional layer can be further improved. In addition, the upper limit of the glass transition temperature of the organic particles is not particularly limited, but is usually 500° C. or lower.

[0090] The glass transition temperature of the organic particles can be adjusted by changing the type and ratio of the monomers used when preparing the organic particles.

[0091] <Water-soluble polymer>

[0092] Water-soluble polymer is a component that mainly contributes to improving the coating stability and slurry stability of the functional layer composition. All along, in order to form a functional layer composition containing non-conductive particles such as organic particles in water, sodium salt of carboxymethyl cellulose, etc. is used to be well coated on a substrate. However, according to the research of the inventors, when sodium salt of carboxymethyl cellulose is used, sometimes the organic particles in the functional layer composition will settle due to coagulation, etc., and the slurry stability is impaired. The reduction of the slurry stability is particularly significant when the volume average particle size of the organic particles is small (for example, less than 500nm). In this regard, if a water-soluble polymer containing a hydroxyl-containing structural unit is used in a ratio of more than 15% by mass and less than 100% by mass, the slurry stability of the functional layer composition containing the organic particles specified above can be fully ensured, and the functional layer composition can be well coated on a substrate. Moreover, it is speculated that in the functional layer obtained using the functional layer composition of the present invention, the specified organic particles that help to improve the heat shrinkage resistance are well arranged without density unevenness due to the action of the above-mentioned water-soluble polymer. Therefore, by using a functional layer composition containing the above-mentioned organic particles and the above-mentioned water-soluble polymer, the heat shrinkage resistance of the functional layer can be greatly improved.

[0093] <<Composition>>

[0094] Here, the water-soluble polymer contains the hydroxyl-containing structural unit at a ratio of 15 mass % to 100 mass % as described above. Furthermore, the water-soluble polymer may contain repeating units (other repeating units) other than the hydroxyl-containing structural unit at a ratio of 85 mass % or less.

[0095] [Hydroxy-containing structural unit]

[0096] The structure of the hydroxyl-containing structural unit is not particularly limited as long as it is a repeating unit having a hydroxyl group. In addition, as a method for introducing a hydroxyl-containing structural unit into a water-soluble polymer, for example, the following method (1) or (2) can be cited:

[0097] (1) A method for preparing a polymer using a monomer composition containing a vinyl carboxylate monomer represented by the general formula: R-CO-O-CH=CH2 (wherein R is an arbitrary structure, preferably an alkyl group having 1 to 19 carbon atoms), and saponifying the polymer to convert R-CO-O- of the vinyl carboxylate monomer unit into a hydroxyl group to prepare a water-soluble polymer containing a vinyl alcohol unit;

[0098] (2) A method for producing a water-soluble polymer containing a hydroxyl-containing monomer unit using a monomer composition containing a hydroxyl-containing monomer.

[0099] Among these, the method (1) is preferred because it can easily produce a water-soluble polymer having a high content ratio of hydroxyl group-containing structural units.

[0100] In addition, examples of the carboxylic acid vinyl ester monomer used in the method (1) include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, and vinyl stearate. These can be used alone or in combination of two or more. Among these, vinyl acetate is preferred.

[0101] In addition, examples of the hydroxyl-containing monomer used in the method (2) include: ethylenically unsaturated alcohols such as (meth)allyl alcohol, 3-butene-1-ol, and 5-hexene-1-ol; alkyl alcohol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconate; general formula: CH2=CR 1 -COO-(C q H 2q O) p -H (wherein p represents an integer of 2 to 9, q represents an integer of 2 to 4, R 1 Esters of polyalkylene glycol represented by alkylene glycol (representing hydrogen or methyl) and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; alkylene glycols such as (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether and (meth)allyl-6-hydroxyhexyl ether Mono(methyl)allyl ethers of alcohols; mono(methyl)allyl ethers of polyoxyalkylene glycols such as diethylene glycol mono(methyl)allyl ether and dipropylene glycol mono(methyl)allyl ether; mono(methyl)allyl ethers of halides and hydroxyl-substituted products of (poly)alkylene glycols such as glycerol mono(methyl)allyl ether, (methyl)allyl-2-chloro-3-hydroxypropyl ether and (methyl)allyl-2-hydroxy-3-chloropropyl ether; mono(methyl)allyl ethers of polyphenols such as eugenol and isoeugenol and halides thereof; (methyl)allyl sulfides of alkylene glycols such as (methyl)allyl-2-hydroxyethyl sulfide and (methyl)allyl-2-hydroxypropyl sulfide; 2-hydroxyethyl (methyl)acrylamide, etc. These can be used alone or in combination of two or more. Among these, 2-hydroxyethylacrylamide is preferred.

[0102] Moreover, when all repeating units of the water-soluble polymer are 100% by mass, the content of the hydroxyl-containing structural unit in the water-soluble polymer needs to be 15% by mass or more and 100% by mass or less, preferably 35% by mass or more, more preferably 50% by mass or more, and further preferably 70% by mass or more. When the content of the hydroxyl-containing structural unit in the water-soluble polymer is less than 15% by mass, the slurry stability of the composition for the functional layer is impaired.

[0103] [Other repeating units]

[0104] As other repeating units arbitrarily included in the water-soluble polymer, there are no particular restrictions. As monomers that can form other repeating units, (meth) acrylamide monomers (acrylamide, methacrylamide, dimethyl acrylamide, etc.), acidic group-containing monomers described in the "organic particles" item, N-vinyl formamide, N-vinyl acetamide, vinyl pyrrolidone, (meth) acryloyl morpholine can be cited. In addition, when the hydroxyl-containing structural unit is introduced into the water-soluble polymer using the method of (1) above, in the water-soluble polymer obtained after saponification, the carboxylic acid vinyl ester monomer unit can also be left as other repeating units.

[0105] Moreover, when all repeating units of the water-soluble polymer are 100% by mass, the content of other repeating units in the water-soluble polymer needs to be 85% by mass or less, preferably 50% by mass or less, and more preferably 15% by mass or less. When the content of other repeating units in the water-soluble polymer exceeds 85% by mass, the slurry stability of the composition for the functional layer is impaired.

[0106] Especially, when all repeating units of water-soluble polymer are 100 mass %, the containing ratio of the acidic group-containing monomeric unit in the water-soluble polymer is preferably below 40 mass %, more preferably below 20 mass %, further preferably below 5 mass %, particularly preferably below 1 mass %, most preferably 0 mass %. The acidic group-containing monomeric unit is identical with the hydroxyl-containing structural unit, and is a repeating unit that can improve the water solubility of polymer, but compared to the hydroxyl-containing structural unit, it is easy to increase the amount of water brought into the secondary battery. Therefore, by making the ratio of the acidic group-containing monomeric unit in the water-soluble polymer be below 40 mass %, the amount of water brought into the secondary battery can be reduced, and the cycle characteristics of the secondary battery are improved.

[0107] <<Preparation method>>

[0108] The method for preparing the water-soluble polymer is not particularly limited. For example, the water-soluble polymer as an addition polymer can be prepared by polymerizing a monomer composition containing the above-mentioned monomers to obtain a polymer and then saponifying the obtained polymer as needed.

[0109] In this case, the content ratio of each monomer in the monomer composition can be determined according to the content ratio of each repeating unit in the water-soluble polymer.

[0110] Moreover, the polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization can be used. In addition, as the polymerization reaction, any reaction such as ionic polymerization, free radical polymerization, living free radical polymerization can also be used. The polymerization conditions can be appropriately adjusted according to the polymerization method, etc.

[0111] Furthermore, known additives such as a polymerization initiator and a chain transfer agent can be used in the polymerization, and the amounts thereof used are also amounts generally used.

[0112] Furthermore, the saponification method is not particularly limited, and a known method can be used.

[0113] <<Electrical Properties of Water>>

[0114] The water-soluble polymer obtained in the above manner may be any of anionic, cationic, and nonionic, preferably nonionic. If a nonionic water-soluble polymer is used, the ionic strength in the functional layer composition can be reduced and the slurry stability of the functional layer composition can be further improved.

[0115] Here, as mentioned above, when the whole repeating units of water-soluble polymer are 100 mass %, nonionic water-soluble polymer comprises nonionic repeating unit with more than 99 mass % and the ratio below 100 mass %.In addition, in the present invention, the meaning of nonionic repeating unit is the repeating unit without acidic group (carboxylic acid group, sulfonic acid group, phosphoric acid group etc.), basic group (amino) etc. ionic functional group.And, as nonionic repeating unit, for example hydroxyl-containing structural unit, (methyl) acrylamide monomer unit, carboxylic acid vinyl ester monomer unit, crosslinking monomer unit, monofunctional (methyl) acrylate monomer unit, N-vinyl formamide unit, N-vinylacetamide unit, vinyl pyrrolidone unit, (methyl) acryloyl morpholine unit can be enumerated.

[0116] <<Weight Average Molecular Weight>>

[0117] In addition, the weight average molecular weight of the water-soluble polymer obtained in the above manner is preferably 10,000 or more, more preferably 22,000 or more, further preferably 30,000 or more, particularly preferably 40,000 or more, preferably 300,000 or less, more preferably 200,000 or less, further preferably 1,000,000 or less, particularly preferably 75,000 or less, and most preferably less than 50,000. If the weight average molecular weight of the water-soluble polymer is 10,000 or more, the rigidity of the functional layer can be improved, and the heat shrinkage resistance can be further improved. On the other hand, if the weight average molecular weight of the water-soluble polymer is 300,000 or less, the viscosity of the composition for the functional layer can be suppressed, and the coating stability can be improved.

[0118] The weight average molecular weight of the water-soluble polymer can be appropriately adjusted by changing the polymerization conditions (such as the type and amount of the polymerization initiator).

[0119] <<Saponification Degree>>

[0120] Moreover, the saponification degree of the water-soluble polymer obtained in the above manner (especially obtained by saponification) is preferably 80 mol% or more, more preferably 85 mol% or more, and further preferably 90 mol% or more. If the saponification degree of the water-soluble polymer is 80 mol% or more, the viscosity increase of the functional layer composition can be suppressed and the coating stability can be improved. In addition, the upper limit of the saponification degree is not particularly limited and can be 100 mol% or less.

[0121] In addition, the saponification degree of the water-soluble polymer can be appropriately adjusted by changing the saponification conditions.

[0122] <<Compound Amount>>

[0123] The amount of the water-soluble polymer in the functional layer composition is not particularly limited, and is preferably 0.1 mass parts or more, more preferably 0.2 mass parts or more, further preferably 2 mass parts or more, particularly preferably 5 mass parts or more, preferably 15 mass parts or less, more preferably 10 mass parts or less, relative to 100 mass parts of organic particles. If the amount of the water-soluble polymer in the functional layer composition is 0.1 mass parts or more relative to 100 mass parts of organic particles, the coating stability of the functional layer composition can be improved, and the slurry stability can be further improved. On the other hand, if the amount of the water-soluble polymer in the functional layer composition is 15 mass parts or less relative to 100 mass parts of organic particles, the heat shrinkage resistance of the functional layer can be fully ensured.

[0124] <Bonding material>

[0125] The composition for a functional layer of the present invention may contain a binder. The binder is a component composed of a polymer and can prevent the components such as the organic particles contained in the functional layer from being separated from the functional layer in the functional layer formed using the composition for a functional layer.

[0126] <<Type>>

[0127] As the binding material optionally included in the composition for the functional layer, there can be mentioned a known particulate polymer (excluding the polymer belonging to the above-mentioned organic particles) that is insoluble in water and can be dispersed in a dispersion medium such as water, such as a thermoplastic elastomer. In addition, as the thermoplastic elastomer, there can be mentioned an acrylic polymer (a polymer containing a monofunctional (meth) acrylate monomer unit), isoprene rubber (IR), natural rubber (NR), nitrile rubber (NBR) (a polymer containing an acrylonitrile monomer and a butadiene monomer), and styrene-butadiene rubber (SBR) (a polymer containing a styrene unit and a butadiene unit).

[0128] These can be used alone or in combination of two or more. Among these, acrylic polymers are preferred.

[0129] <<Glass Transition Temperature>>

[0130] The glass transition temperature of the adhesive material is preferably -40°C or higher, preferably 0°C or lower, and more preferably -15°C or lower. If the glass transition temperature of the adhesive material is -40°C or higher, the adhesion of the battery component having the functional layer can be suppressed. On the other hand, if the glass transition temperature of the adhesive material is 0°C or lower, the adhesion of the functional layer can be sufficiently ensured.

[0131] In addition, the glass transition temperature of the adhesive material can be adjusted by changing the type and proportion of the monomers used in preparing the adhesive material. For example, by increasing the proportion of aromatic monovinyl monomers such as acrylonitrile or styrene used in preparing the adhesive material, the glass transition temperature of the adhesive material can be increased; by reducing the proportion, the glass transition temperature of the adhesive material can be reduced.

[0132] <<Compound Amount>>

[0133] The amount of the binder in the functional layer composition is not particularly limited, but is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and preferably 20 parts by mass or less, more preferably 15 parts by mass or less, based on 100 parts by mass of the organic particles.

[0134] <Inorganic particles>

[0135] The composition for a functional layer of the present invention may contain inorganic particles. The inorganic particles are the same as the above-mentioned organic particles, and are both non-conductive particles, and are components that mainly improve the heat shrinkage resistance, strength, etc. of the functional layer.

[0136] <<Type>>

[0137] As inorganic particles arbitrarily included in the composition for the functional layer, there can be mentioned: oxide particles such as aluminum oxide (alumina), hydrated aluminum oxide (boehmite (AlOOH), gibbsite (Al(OH)3), silicon oxide, magnesium oxide (magnesi a), calcium oxide, titanium oxide (titania), barium titanate (BaTiO3), ZrO, and aluminum oxide-silicon dioxide composite oxide; nitride particles such as aluminum nitride and boron nitride; covalently bonded crystal particles such as silicon and diamond; insoluble ionic crystal particles such as barium sulfate, calcium fluoride, and barium fluoride; clay particles such as talc and montmorillonite, etc. In addition, these particles can also be subjected to element replacement, surface treatment, solid solution, etc. as needed. These can be used alone or in combination of two or more. Among these, boehmite particles, barium sulfate particles, and aluminum oxide particles are preferred as inorganic particles.

[0138] <<Compound Amount>>

[0139] The amount of inorganic particles in the functional layer composition is not particularly limited. However, from the viewpoint of suppressing the increase of the amount of water brought into the secondary battery from the bound water and hydrated water on the surface of the inorganic particles, and fully improving the slurry stability of the functional layer composition, and improving the cycle characteristics of the secondary battery, relative to 100 parts by mass of organic particles, the amount of inorganic particles is preferably less than 100 parts by mass, more preferably less than 50 parts by mass, further preferably less than 30 parts by mass, and particularly preferably less than 10 parts by mass.

[0140] <Other ingredients>

[0141] As the composition for the functional layer of the present invention, in addition to organic particles, water-soluble polymers, binding materials, inorganic particles and water and other dispersion media, the composition that can also be contained is not particularly limited. As such a component, known additives can be cited. As a known additive, it is not particularly limited, and components such as surface tension modifiers, dispersants, viscosity modifiers, wetting agents, reinforcing agents, electrolyte additives can be contained. These are not particularly limited as long as they do not affect the battery reaction, and known components can be used, such as the components described in International Publication No. 2012 / 115096. In addition, these other components can be used alone, or two or more can be used in combination in any ratio.

[0142] <Method for preparing composition for non-aqueous secondary battery functional layer>

[0143] Furthermore, the composition for the functional layer of the present invention is not particularly limited except that it contains the above-mentioned prescribed organic particles, water-soluble polymers, and water as a dispersion medium, and can be prepared, for example, by stirring and mixing the organic particles, water-soluble polymers, and the above-mentioned binding materials and inorganic particles and other components that can be added arbitrarily in the presence of water. In addition, when the composition for the functional layer is prepared using a dispersion of organic particles or an aqueous solution of a water-soluble polymer, the water contained in the dispersion and / or aqueous solution can be directly used as the dispersion medium of the composition for the functional layer.

[0144] Here, the stirring method is not particularly limited and can be carried out by a known method. Specifically, a general stirring container, a ball mill, a sand mill, a bead mill, a pigment disperser, an ultrasonic disperser, a grinding and crushing machine, a homogenizer, a planetary mixer, Filmix, etc. can be used to mix the above-mentioned components with a dispersion medium containing water, thereby preparing a slurry-like functional layer composition. In addition, the mixing of the above-mentioned components and the dispersion medium containing water can usually be carried out in the range of room temperature to 80°C for 10 minutes to several hours.

[0145] (Functional layer for non-aqueous secondary batteries)

[0146] The functional layer of the present invention is formed by the above-mentioned functional layer composition, and after forming a film by, for example, applying the above-mentioned functional layer composition on a suitable substrate surface, the formed film is dried to form the functional layer of the present invention. That is, the functional layer of the present invention is composed of the dried product of the above-mentioned functional layer composition, containing the above-mentioned organic particles and water-soluble polymers, and arbitrarily containing the above-mentioned binding material, the above-mentioned inorganic particles and the above-mentioned other components. In addition, components such as organic particles can be cross-linked (that is, the functional layer of the present invention can include, for example, a cross-linked product of organic particles) when the functional layer composition is dried or arbitrarily implemented after drying. In addition, the various components included in the functional layer are those included in the above-mentioned functional layer composition, and the preferred existence ratio of these various components is the same as the preferred existence ratio of the various components in the functional layer composition.

[0147] Furthermore, the functional layer of the present invention is formed using the above-mentioned functional layer composition, so it has excellent heat shrinkage resistance and suppresses streaks and uneven coating. Therefore, if a battery component having the functional layer is used, a secondary battery with fully ensured battery characteristics such as cycle characteristics can be obtained.

[0148] <Base Material>

[0149] Here, the substrate for coating the composition for the functional layer is not limited, for example, a coating film of the composition for the functional layer can be formed on the surface of the release substrate, the coating film is dried to form a functional layer, and the release substrate is peeled off from the functional layer. The functional layer peeled off from the release substrate like this can also be used as a self-supporting film to form a battery component of a secondary battery. Specifically, the functional layer peeled off from the release substrate can be stacked on a spacer substrate to form a spacer having a functional layer, and the functional layer peeled off from the release substrate can also be stacked on an electrode substrate to form an electrode having a functional layer.

[0150] However, from the viewpoint of omitting the step of peeling off the functional layer and improving the production efficiency of the battery member, it is preferable to use a separator substrate or an electrode substrate as the substrate.

[0151] <<Spacer Base Material>>

[0152] There is no particular limitation on the spacer substrate, and known spacer substrates such as organic spacer substrates can be cited. The organic spacer substrate is a porous member formed of an organic material. When an example of an organic spacer substrate is cited, a microporous membrane or non-woven fabric containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, etc. can be cited. Microporous membranes and non-woven fabrics made of polyethylene are preferred due to their excellent strength. In addition, the thickness of the spacer substrate can be any thickness, preferably 5 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less, and further preferably 5 μm or more and 18 μm or less. If the thickness of the spacer substrate is 5 μm or more, sufficient safety can be obtained. In addition, if the thickness of the spacer substrate is 30 μm or less, it is possible to suppress the decrease in ion conductivity and the decrease in the output characteristics of the secondary battery, and it is possible to suppress the increase in the thermal shrinkage force of the spacer substrate and improve heat resistance.

[0153] <<Electrode Base Material>>

[0154] The electrode substrate (positive electrode substrate and negative electrode substrate) is not particularly limited, and examples thereof include an electrode substrate in which an electrode composite material layer is formed on a current collector.

[0155] Here, the current collector, the electrode active material (positive electrode active material, negative electrode active material) in the electrode composite material layer, the binding material for the electrode composite material layer (binding material for the positive electrode composite material layer, binding material for the negative electrode composite material layer), and the method for forming the electrode composite material layer on the current collector can use known materials and methods, for example, the materials and methods described in Japanese Patent Gazette No. 2013-145763 can be used.

[0156] <Method for forming a functional layer for a non-aqueous secondary battery>

[0157] As a method for forming a functional layer on the substrate such as the separator substrate and the electrode substrate, the following method can be mentioned.

[0158] 1) A method of applying the composition for a functional layer of the present invention on the surface of a separator substrate or an electrode substrate (in the case of an electrode substrate, the surface on the electrode composite material layer side, the same below), and then drying;

[0159] 2) A method of dipping a separator substrate or an electrode substrate into the composition for a functional layer of the present invention and then drying the substrate; and

[0160] 3) A method in which the functional layer composition of the present invention is applied to a release substrate and dried to produce a functional layer, and the obtained functional layer is transferred to the surface of a separator substrate or an electrode substrate.

[0161] Among these, the method 1) is particularly preferred because it is easy to control the thickness of the functional layer. Specifically, the method 1) includes a step of applying a functional layer composition on a substrate (coating step), and a step of drying the functional layer composition applied on the substrate to form a functional layer (functional layer forming step).

[0162] In addition, the functional layer may be formed only on one side of the separator substrate or the electrode substrate, or may be formed on both sides, depending on the structure of the secondary battery to be manufactured. Here, when a separator substrate is used as the substrate, the functional layer is preferably formed on both sides of the separator substrate; when an electrode substrate is used as the substrate, the functional layer is preferably formed on one side of the electrode substrate, especially on the electrode composite material layer.

[0163] <<Coating process>>

[0164] In the coating step, the method for coating the functional layer composition on the substrate is not particularly limited, and examples thereof include doctor blade coating, reverse roll coating, direct roll coating, gravure printing, extrusion, and brush coating.

[0165] <<Functional layer forming step>>

[0166] In addition, in the functional layer forming step, the method for drying the functional layer composition on the substrate is not particularly limited, and a known method can be used. Examples of the drying method include: drying using warm air, hot air, or low-humidity air; vacuum drying; and drying using irradiation of infrared rays, electron beams, and the like. The drying conditions are not particularly limited, but the drying temperature is preferably 40 to 150° C., and the drying time is preferably 2 to 30 minutes.

[0167] <Thickness of Functional Layer>

[0168] Moreover, the thickness of each functional layer formed on the substrate is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.3 μm or more, preferably 5 μm or less, more preferably 2 μm or less, and further preferably 1 μm or less. If the thickness of the functional layer is 0.1 μm or more, the heat shrinkage resistance of the functional layer can be fully ensured. On the other hand, if the thickness of the functional layer is 5 μm or less, the functional layer can be thinned, thereby helping to increase the capacity of the secondary battery.

[0169] In addition, in the present invention, the "thickness" of the functional layer can be measured using the method described in the Examples of this specification.

[0170] (Non-aqueous secondary battery components)

[0171] The battery component of the present invention has the above-mentioned functional layer of the present invention. By using this battery component, a secondary battery can be obtained which can fully ensure safety and can exhibit good battery characteristics such as cycle characteristics.

[0172] Here, the battery component of the present invention generally has a substrate and the above-mentioned functional layer of the present invention, and specifically, a separator having a separator substrate and the functional layer of the present invention, and an electrode having an electrode substrate and the functional layer of the present invention can be mentioned. Here, as the electrode substrate and the separator substrate, the same ones as those listed in the item "functional layer for non-aqueous secondary battery" can be used.

[0173] Furthermore, the battery member (separator and electrode) of the present invention may have structural elements other than the separator substrate or the electrode substrate and the functional layer of the present invention unless the effects of the present invention are significantly impaired.

[0174] (Non-aqueous secondary battery)

[0175] The secondary battery of the present invention is a secondary battery having the battery component of the present invention described above. More specifically, the secondary battery of the present invention has a positive electrode, a negative electrode, a separator and an electrolyte, and uses the battery component of the present invention as at least one selected from the positive electrode, the negative electrode and the separator.

[0176] <Positive Electrode, Negative Electrode and Separator>

[0177] As described above, at least one of the positive electrode, negative electrode and separator used in the secondary battery of the present invention is the battery member of the present invention. In other words, in the secondary battery of the present invention, at least one of the positive electrode, negative electrode and separator has the functional layer of the present invention.

[0178] The positive electrode, negative electrode, and separator having no functional layer are not particularly limited, and the electrodes formed of the above-mentioned electrode substrates and the separator formed of the above-mentioned separator substrates can be used.

[0179] <Electrolyte>

[0180] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent can generally be used. As a supporting electrolyte, a lithium salt can be used in, for example, a lithium ion secondary battery. As a lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Among them, LiPF6, LiClO4, and CF3SO3Li are preferred because they are easily soluble in solvents and show a high degree of dissociation. In addition, one electrolyte can be used alone, or two or more electrolytes can be used in combination. Generally, there is a tendency that the lithium ion conductivity becomes higher when a supporting electrolyte with a high degree of dissociation is used, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.

[0181] As an organic solvent used in the electrolyte, there is no particular limitation as long as it can dissolve the supporting electrolyte. For example, in lithium-ion secondary batteries, it is preferred to use carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), and carbonate vinylene ester (VC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide. In addition, a mixed solution of these solvents can also be used. Among them, carbonates are preferred because of their high dielectric constant and wide stable potential region. There is usually a tendency that the lower the viscosity of the solvent used, the higher the lithium ion conductivity becomes, so the lithium ion conductivity can be adjusted by the type of solvent.

[0182] In addition, the concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. In addition, a known additive can be added to the electrolytic solution.

[0183] <Method for producing non-aqueous secondary battery>

[0184] The above-mentioned non-aqueous secondary battery of the present invention can be manufactured by, for example, the following manner, the positive electrode and the negative electrode are overlapped across a spacer, and are wound, folded, etc. as needed and placed in a battery container, and the electrolyte is injected into the battery container for sealing. In addition, at least one battery component in the positive electrode, the negative electrode, and the spacer is a battery component with a functional layer. In addition, porous metal mesh, fuse, PTC element and other anti-overcurrent components, guide plates, etc. can also be placed in the battery container as needed to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can also be any of, for example, coin-type, button-type, sheet-type, cylindrical, square, flat, etc.

[0185] Example

[0186] Hereinafter, the present invention will be specifically described based on the examples, but the present invention is not limited to these examples. In addition, in the following description, unless otherwise specified, the "%" and "parts" indicating the amount are weight references. In addition, in the present invention, unless otherwise specified, in a polymer manufactured by copolymerizing a plurality of monomers, the "content ratio of monomer units" formed by polymerizing a certain monomer is usually consistent with the ratio (feed ratio) of the certain monomer in all the monomers used in the polymerization of the polymer.

[0187] Moreover, in the embodiments and comparative examples, the glass transition temperature and volume average particle size of the organic particles and the binding material, the saponification degree and weight average molecular weight of the water-soluble polymer, the coating stability and slurry stability of the composition for the functional layer, the thickness, moisture content and heat shrinkage resistance of the functional layer, and the cycle characteristics of the secondary battery were evaluated according to the following methods.

[0188] <Glass transition temperature (Tg)>

[0189] The aqueous dispersions of the organic particles and the binder were dried at 25° C. for 24 hours to obtain measurement samples.

[0190] 10 mg of the sample was weighed in an aluminum dish, and an empty aluminum dish was used as a reference. The DSC curve was measured at room temperature and humidity by a differential thermal analysis measuring apparatus (manufactured by SII Nano Technology Inc., "EXSTAR DSC6220") in the measuring temperature range of -100°C to 200°C, at a heating rate of 10°C / min. In the heating process, the intersection of the baseline just before the endothermic peak of the DSC curve with a differential signal (DDSC) of 0.05 mW / min / mg or more and the tangent line of the DSC curve at the first inflection point after the endothermic peak was determined, and the intersection was taken as the glass transition temperature (Tg).

[0191] <Volume Average Particle Size>

[0192] The solid content concentration of the aqueous dispersion of organic particles and the binder is adjusted to 0.1% each, and the aqueous dispersion for measurement is prepared. The particle size distribution is measured by a laser diffraction particle size distribution measuring device (Beckman Coulter Inc., product name "LS-230") using the aqueous dispersion for measurement. Then, in the measured particle size distribution, the particle size at which the cumulative volume calculated from the small diameter side becomes 50% is taken as the volume average particle size (D50).

[0193] <Saponification degree>

[0194] The saponification degree of the water-soluble polymer is measured in accordance with the method described in "Testing methods for polyvinyl alcohol" of "JIS K 6726".

[0195] <Weight Average Molecular Weight>

[0196] The measurement was carried out under the following conditions.

[0197] Apparatus: Gel Permeation Chromatography (GPC)

[0198] Chromatographic columns: 1 PWXL guard column made by Tosoh Corporation, 1 GMPWXL, 1 G2500P WXL (temperature: 45°C)

[0199] Eluent: 0.1 mol / L sodium nitrate aqueous solution

[0200] Flow rate: 0.5ml / min

[0201] Detector: Showa Denko K.K. "Differential Refractometer RI-201 (Sensitivity 16)"

[0202] Prepare materials: monodisperse polyethylene oxide, polyethylene glycol

[0203] Measurement sample: After adjusting the concentration to 0.3% using an eluent, the filtrate was filtered through a 0.45 μm filter and then measured.

[0204] <Coating stability>

[0205] In Examples 1 to 9, 11 and Comparative Examples 1 to 4, the obtained composition for the functional layer was applied to a polyethylene separator substrate (manufactured by Asahi Kasei Corporation, product name "MD412") and dried at 50°C for 3 minutes to obtain an evaluation battery member (separator) having a functional layer (thickness: 0.5 μm) on one side. In Example 10, the obtained composition for the functional layer was applied to the obtained negative electrode substrate and dried at 50°C for 3 minutes to obtain an evaluation battery member (negative electrode) having a functional layer (thickness: 0.5 μm) on one side.

[0206] Ten A4-sized (210 mm × 297 mm) test pieces were cut out from the battery component for evaluation obtained above. The surface of the functional layer side of the test piece was observed with the naked eye and evaluated according to the following criteria. The less streaks and coating unevenness were observed, the better the coating stability of the functional layer composition was.

[0207] A: No more than 2 test pieces were observed with streaks and / or uneven coating

[0208] B: Streaks and / or uneven coating were observed on 3 or more and 5 or less test pieces

[0209] C: Streaks and / or uneven coating were observed on 6 or more test pieces

[0210] <Slurry stability>

[0211] 100 ml of the functional layer composition was added to a 100 ml measuring cylinder and allowed to stand, and the appearance was observed every hour. Then, the time required for a clear layer with a vertical width of 5 mm or more to be observed on the upper part of the functional layer composition was set as the sedimentation time, and the evaluation was performed according to the following criteria. The longer the sedimentation time, the better the slurry stability of the functional layer composition.

[0212] A: The sedimentation time is more than 24 hours

[0213] B: The sedimentation time is more than 12 hours and less than 24 hours

[0214] C: Settling time is less than 12 hours

[0215] <Thickness>

[0216] The thickness of the functional layer is calculated by subtracting the thickness of the substrate without the functional layer from the thickness of the battery component formed by laminating the functional layer and the substrate (separator substrate or electrode substrate). In addition, the thickness of the battery component and the substrate are each measured at 10 random locations using a contact thickness gauge (digital indicator No.: 543-575, manufactured by Mitutoyo Corporation) and the average value thereof is calculated.

[0217] <Water content>

[0218] The functional layer composition was applied onto a polyethylene separator substrate (manufactured by Asahi Kasei Corporation, product name "MD412") and dried at 50°C for 3 minutes to obtain an evaluation separator having a functional layer (thickness: 0.5 μm) on one surface.

[0219] The prepared evaluation spacer was cut into a 10 cm wide x 10 cm long test piece. The test piece was placed at a temperature of 25°C and a dew point of -60°C for 24 hours. After that, the moisture content of the test piece was measured by the Karl Fischer method (JIS K-0068 (2001) moisture vaporization method, vaporization temperature 150°C) using a coulometric moisture meter, and evaluated according to the following criteria. The smaller the moisture value, the lower the moisture content of the test piece as a whole and the functional layer.

[0220] A: Moisture content is less than 250 ppm by mass

[0221] B: Water content is 250 mass ppm or more and less than 400 mass ppm

[0222] C: Moisture content is 400ppm or more

[0223] <Heat shrinkage resistance>

[0224] The functional layer composition was applied onto a polyethylene separator substrate (manufactured by Asahi Kasei Corporation, product name "MD412") and dried at 50°C for 3 minutes to obtain an evaluation separator having a functional layer (thickness: 0.5 μm) on one surface.

[0225] The prepared evaluation spacer was cut into a 12 cm × 12 cm square, and a 10 cm square was drawn inside the square as a test piece. Then, the test piece was placed in a 130°C constant temperature bath for 1 hour, and the area change of the square drawn inside (= {(area of ​​the square before placement - area of ​​the square after placement) / area of ​​the square before placement} × 100%) was calculated as the heat shrinkage rate, and evaluated according to the following criteria. The smaller the heat shrinkage rate, the better the heat shrinkage resistance of the functional layer.

[0226] A: Thermal shrinkage is less than 5%

[0227] B: Thermal shrinkage is 5% or more and less than 10%

[0228] C: Thermal shrinkage is more than 10%

[0229] <Cyclic Characteristics>

[0230] Under 25°C environment, the secondary battery is charged to 4.35V and discharged to 3V by the constant current method of 0.2C for 100 times (= 100 cycles). At this time, the discharge capacity X1 of the 5th cycle and the discharge capacity X2 of the 100th cycle are measured, and the capacity retention rate (%) = (X2 / X1) × 100 is calculated. This operation is performed on a total of 10 secondary batteries, and the average value of the capacity retention rate (average capacity retention rate) is calculated and evaluated according to the following criteria. The larger the value of the average capacity retention rate, the better the secondary battery cycle characteristics.

[0231] A: The average capacity retention rate is more than 80%

[0232] B: Average capacity retention rate is 70% or more and less than 80%

[0233] C: Average capacity retention rate is less than 70%

[0234] (Example 1)

[0235] <Preparation of organic particles>

[0236] In a reactor A having a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate and 100 parts of ion exchange water are added and mixed to form a mixture, and the temperature is raised to 80°C. On the other hand, 100 parts of n-butyl acrylate as a monofunctional (meth) acrylate monomer, 0.8 parts of sodium dodecylbenzenesulfonate and 100 parts of ion exchange water are mixed in another container to prepare a monomer composition for seed particles. The monomer composition for seed particles is continuously added to the above-mentioned reactor A for 4 hours to carry out a polymerization reaction. The temperature in the reactor during the continuous addition of the monomer composition for seed particles is maintained at 80°C. In addition, after the continuous addition is completed, the polymerization reaction is further continued at 90°C for 3 hours. Thus, an aqueous dispersion of seed particles is obtained. In addition, the volume average particle size of the seed particles is measured in the same manner as the organic particles, and the result is 120nm.

[0237] Next, in a reactor equipped with a stirrer, 16 parts of the above-mentioned aqueous dispersion of seed particles, 82 parts of ethylene glycol dimethacrylate (manufactured by KYOEISHA CHEMICAL Co., LTD., product name "Light Ester EG") as a multifunctional monomer, 2 parts of acrylic acid as an acidic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of tert-butyl 2-ethylperoxyhexanoate (manufactured by NOF CORPORATION, product name "PERB UTYL O") as a polymerization initiator and 200 parts of ion exchange water were added, and stirred at 35° C. for 12 hours, so that the seed particles completely absorbed the multifunctional monomer, the acidic group-containing monomer and the polymerization initiator. Then, the temperature in the reactor was maintained at 90° C., and a polymerization reaction (seed polymerization) was performed for 5 hours.

[0238] Next, steam was introduced to remove unreacted monomers and initiator decomposition products to obtain an aqueous dispersion of organic particles. Then, the volume average particle size and glass transition temperature of the obtained organic particles were measured. The results are shown in Table 1. In addition, regarding the glass transition temperature, since no peak was confirmed within the measurement temperature range, it was judged to be more than 200°C (the same applies to Examples 2 to 11).

[0239] <Preparation of water-soluble polymer>

[0240] Polyvinyl alcohol (manufactured by KURARAY CO., LTD., product name "PVA110") was prepared as a water-soluble polymer. The water-soluble polymer was added to ion-exchanged water and stirred at 80°C for 1 hour to obtain an aqueous solution of the water-soluble polymer (solid content concentration: 5%).

[0241] <Preparation of bonding material>

[0242] In a reactor B equipped with a stirrer, 70 parts of ion exchange water, 0.15 parts of sodium dodecyl sulfate (manufactured by Kao Corporation, product name "Emal 2F") as an emulsifier, and 0.5 parts of ammonium persulfate were supplied, and the gas phase was replaced with nitrogen and heated to 60° C. On the other hand, 50 parts of ion exchange water, 0.7 parts of sodium dodecylbenzenesulfonate as a dispersant, 96 parts of n-butyl acrylate as a monomer, 2 parts of acrylonitrile as a monomer, and 2 parts of methacrylic acid as a monomer were mixed in another container to obtain a monomer composition.

[0243] The monomer mixture was continuously added to the reactor B over 4 hours to perform polymerization. During the continuous addition, the reaction was performed at 60° C. After the continuous addition was completed, the reaction was terminated by stirring at 70° C. for 3 hours to obtain an aqueous dispersion of a binder (acrylic polymer).

[0244] The obtained binder had a volume average particle size of 200 nm and a glass transition temperature of -35°C.

[0245] <Preparation of Composition for Functional Layer>

[0246] 100 parts (in terms of solid content) of the above organic particles and 5 parts (in terms of solid content) of the above water-soluble polymer were mixed in a stirring container, and 10 parts (in terms of solid content) of the above binder were further added and mixed. Ion exchange water was added to the obtained mixed solution to prepare a functional layer composition (solid content concentration: 10%). The obtained functional layer composition was used to evaluate coating stability, slurry stability, and moisture content and heat shrinkage resistance of the functional layer. The results are shown in Table 1.

[0247] <Production of a spacer having functional layers on both sides>

[0248] The functional layer composition was applied to a polyethylene spacer substrate (manufactured by Asahi Kasei Corporation, product name "MD412") and dried at 50°C for 3 minutes to form a functional layer (thickness: 0.5 μm). Furthermore, the functional layer composition was also applied to the other side of the spacer substrate, and the functional layer composition on the spacer substrate was dried at 50°C for 3 minutes to form a functional layer (thickness: 0.5 μm), thereby preparing a spacer having functional layers on both sides.

[0249] <Production of negative electrode>

[0250] In a 5MPa pressure-resistant container with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion exchange water and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 50°C to initiate polymerization. When the polymerization conversion rate reached 96%, the mixture was cooled and the reaction was terminated to obtain a mixture containing a negative electrode binder (SBR). After adding 5% sodium hydroxide aqueous solution to the mixture containing the above-mentioned negative electrode binder and adjusting it to pH 8, the unreacted monomers were removed by heating and reduced pressure distillation. Next, it was cooled to below 30°C to obtain an aqueous dispersion containing the desired negative electrode binder.

[0251] After mixing 100 parts of artificial graphite (volume average particle size: 15.6 μm) as a negative electrode active material and 1 part (in terms of solid content equivalent) of a 2% aqueous solution of sodium carboxymethyl cellulose (NIPPON PAPER INDUSTRIES CO., LTD., product name "MAC350HC") as a thickener, the solid content concentration was adjusted to 68% using ion exchange water, and then mixed at 25°C for 60 minutes. Furthermore, after adjusting the solid content concentration to 62% using ion exchange water, mix at 25°C for 15 minutes. To the obtained mixed solution, 1.5 parts of the above-mentioned negative electrode binder and ion exchange water were added in terms of solid content equivalent, and the final solid content concentration was adjusted to 52%, and further mixed for 10 minutes. It was degassed under reduced pressure to obtain a negative electrode slurry composition with good fluidity.

[0252] The negative electrode slurry composition obtained above is applied on a copper foil with a thickness of 20 μm as a current collector using a notch wheel coater so that the film thickness after drying is about 150 μm, and it is dried. The drying is carried out by conveying the copper foil in an oven at 60 ° C for 2 minutes at a speed of 0.5 m / min. Then, the negative electrode raw material before pressing is obtained by heating at 120 ° C for 2 minutes. The negative electrode raw material before pressing is rolled using a roller press to obtain a negative electrode (single-sided negative electrode) with a thickness of 80 μm of the negative electrode composite material layer after pressing.

[0253] <Production of positive electrode>

[0254] A planetary mixer was used to mix 100 parts of LiCoO2 (volume average particle size: 12 μm) as a positive electrode active material, 2 parts of acetylene black (manufactured by Denka Company Limited, product name "HS-100") as a conductive material, 2 parts (in terms of solid content equivalent) of PVDF (manufactured by KUREHA CORPORATION, product name "#7208") as a positive electrode binding material, and NMP to obtain a positive electrode slurry composition (solid content concentration: 70%).

[0255] The positive electrode slurry composition obtained above is applied on an aluminum foil with a thickness of 20 μm as a current collector using a notch wheel coater so that the film thickness after drying is about 150 μm, and it is dried. The drying is carried out by conveying the aluminum foil in an oven at 60 ° C for 2 minutes at a speed of 0.5 m / min. Then, the positive electrode raw material before pressing is obtained by heating at 120 ° C for 2 minutes. The positive electrode raw material before pressing is rolled using a roller press to obtain a positive electrode (single-sided positive electrode) with a thickness of 80 μm of the positive electrode composite material layer after pressing.

[0256] <Manufacturing of Secondary Battery>

[0257] The pressed positive electrode obtained by the above is cut into 49cm×5cm and placed on the table in such a way that the surface on the positive electrode composite material layer side becomes the upper side. Then, a separator cut into 120cm×5.5cm is arranged on the positive electrode composite material layer of the positive electrode. Furthermore, the negative electrode obtained by the above is cut into 50cm×5.2cm, and the negative electrode is arranged on the above separator in such a way that the surface on the negative electrode active material layer side is opposite to the separator, thereby obtaining a laminate. The laminate is wound using a winding machine to obtain a wound body. Furthermore, the wound body is pressed at 60°C and 0.5MPa to form a flat body. Then, the flat body is wrapped with an aluminum packaging material outer packaging as the outer packaging of the battery, and the electrolyte (solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate (volume mixing ratio) = 68.5 / 30 / 1.5, electrolyte: LiPF6 with a concentration of 1M) is injected in a manner to exhaust the air. Next, in order to seal the opening of the aluminum packaging material, the opening of the aluminum outer package was sealed by heat sealing at 150°C, and the wound body and the aluminum packaging material outer package were pressed at 60°C and 0.5 MPa to produce a 1000 mAh wound lithium ion secondary battery. The cycle characteristics of the obtained lithium ion secondary battery were evaluated. The results are shown in Table 1.

[0258] (Examples 2, 3, 7)

[0259] As a water-soluble polymer, instead of polyvinyl alcohol (KURARAY CO., LTD., product name "PVA110"), polyvinyl alcohol (KURARAY CO., LTD., product name "PVA117") (Example 2), polyvinyl alcohol (KURARAY CO., LTD., product name "PVA105") (Example 3), polyvinyl alcohol (KURARAY CO., LTD., product name "PVA210") (Example 7) were used, and organic particles, binding materials, functional layer compositions, separators, negative electrodes, positive electrodes, and secondary batteries were manufactured in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0260] (Example 4)

[0261] The water-soluble polymer was prepared in the same manner as in Example 1, and a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 1, except that the organic particles prepared as follows were used. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0262] <Preparation of organic particles>

[0263] In a reactor A having a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate and 100 parts of ion exchange water are added and mixed to form a mixture, and the temperature is raised to 80°C. On the other hand, 100 parts of n-butyl acrylate as a monofunctional (meth) acrylate monomer, 0.6 parts of sodium dodecylbenzenesulfonate and 100 parts of ion exchange water are mixed in another container to prepare a monomer composition for seed particles. The monomer composition for seed particles is continuously added to the above-mentioned reactor A for 4 hours to carry out a polymerization reaction. The temperature in the reactor during the continuous addition of the monomer composition for seed particles is maintained at 80°C. In addition, after the continuous addition is completed, the polymerization reaction is further continued at 90°C for 3 hours. Thus, an aqueous dispersion of seed particles is obtained. In addition, the volume average particle size of the seed particles is measured in the same manner as the organic particles, and the result is 160nm.

[0264] Next, in a reactor with a stirrer, 48 parts of the above-mentioned aqueous dispersion of seed particles, 50 parts of ethylene glycol dimethacrylate (KYOEISHA CHEMICAL Co., LTD., product name "Light Ester EG") as a multifunctional monomer, 2 parts of acrylic acid as an acidic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of tert-butyl 2-ethylperoxyhexanoate (NOF CORPORATION, product name "PERBUTYL O") as a polymerization initiator and 200 parts of ion exchange water were added, and stirred at 35° C. for 12 hours, so that the seed particles completely absorbed the multifunctional monomer, the acidic group-containing monomer and the polymerization initiator. Then, the temperature in the reactor was maintained at 90° C., and a polymerization reaction (seed polymerization) was performed for 5 hours.

[0265] Next, steam is introduced to remove unreacted monomers and initiator decomposition products, thereby obtaining an aqueous dispersion of organic particles.

[0266] (Example 5)

[0267] The water-soluble polymer was prepared in the same manner as in Example 1, and a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 1, except that the organic particles prepared as follows were used. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0268] <Preparation of organic particles>

[0269] In a reactor A having a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate and 100 parts of ion exchange water are added and mixed to form a mixture, and the temperature is raised to 80°C. On the other hand, 100 parts of n-butyl acrylate as a monofunctional (meth) acrylate monomer, 0.4 parts of sodium dodecylbenzenesulfonate and 100 parts of ion exchange water are mixed in another container to prepare a monomer composition for seed particles. The monomer composition for seed particles is continuously added to the above-mentioned reactor A for 4 hours to carry out a polymerization reaction. The temperature in the reactor during the continuous addition of the monomer composition for seed particles is maintained at 80°C. In addition, after the continuous addition is completed, the polymerization reaction is further continued at 90°C for 3 hours. Thus, an aqueous dispersion of seed particles is obtained. In addition, the volume average particle size of the seed particles is measured in the same manner as the organic particles, and the result is 200nm.

[0270] Next, in a reactor with a stirrer, 73 parts of the above-mentioned aqueous dispersion of seed particles, 25 parts of ethylene glycol dimethacrylate (KYOEISHA CHEMICAL Co., LTD., product name "Light Ester EG") as a multifunctional monomer, 2 parts of acrylic acid as an acidic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of tert-butyl 2-ethylperoxyhexanoate (NOF CORPORATION, product name "PERBUTYL O") as a polymerization initiator and 200 parts of ion exchange water were added, and stirred at 35° C. for 12 hours, so that the seed particles completely absorbed the multifunctional monomer, the acidic group-containing monomer and the polymerization initiator. Then, the temperature in the reactor was maintained at 90° C., and a polymerization reaction (seed polymerization) was performed for 5 hours.

[0271] Next, steam is introduced to remove unreacted monomers and initiator decomposition products, thereby obtaining an aqueous dispersion of organic particles.

[0272] (Example 6)

[0273] Organic particles, a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were produced in the same manner as in Example 1 except that the water-soluble polymer prepared as described below was used. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0274] <Preparation of water-soluble polymer>

[0275] In a four-necked flask with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 35 parts of 2-hydroxyethyl acrylamide as a hydroxyl-containing monomer, 35 parts of acrylamide as a (meth) acrylamide monomer, 30 parts of acrylic acid as an acidic group-containing monomer, 365 parts of ion exchange water and 5 parts of isopropanol were added, and nitrogen was used to remove oxygen in the reaction system. Next, under stirring, 7 parts of a 5% aqueous solution of ammonium persulfate and 3 parts of a 5% aqueous solution of sodium bisulfite as a polymerization initiator were added to the flask, and the temperature was raised from room temperature to 80°C and kept warm for 3 hours. Then, 162 parts of ion exchange water were added, and the pH was adjusted to 5 by 48% sodium hydroxide. Further ion exchange water was added to obtain an aqueous solution of a water-soluble polymer (solid content concentration: 5%).

[0276] (Example 8)

[0277] The water-soluble polymer was prepared in the same manner as in Example 1, and a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 1, except that the organic particles prepared as follows were used. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0278] <Preparation of organic particles>

[0279] In a reactor A having a stirrer, 0.05 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate and 100 parts of ion exchange water are added and mixed to form a mixture, and the temperature is raised to 80°C. On the other hand, 100 parts of n-butyl acrylate as a monofunctional (meth) acrylate monomer, 0.4 parts of sodium dodecylbenzenesulfonate and 100 parts of ion exchange water are mixed in another container to prepare a monomer composition for seed particles. The monomer composition for seed particles is continuously added to the above-mentioned reactor A for 4 hours to carry out a polymerization reaction. The temperature in the reactor during the continuous addition of the monomer composition for seed particles is maintained at 80°C. In addition, after the continuous addition is completed, the polymerization reaction is further continued at 90°C for 3 hours. Thus, an aqueous dispersion of seed particles is obtained. In addition, the volume average particle size of the seed particles is measured in the same manner as the organic particles, and the result is 380nm.

[0280] Next, in a reactor with a stirrer, 16 parts of the above-mentioned aqueous dispersion of seed particles, 82 parts of ethylene glycol dimethacrylate (KYOEISHA CHEMICAL Co., LTD., product name "Light Ester EG") as a multifunctional monomer, 2 parts of acrylic acid as an acidic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of tert-butyl 2-ethylperoxyhexanoate (NOF CORPORATION, product name "PERBUTYL O") as a polymerization initiator and 200 parts of ion exchange water were added, and stirred at 35° C. for 12 hours, so that the seed particles completely absorbed the multifunctional monomer, the acidic group-containing monomer and the polymerization initiator. Then, the temperature in the reactor was maintained at 90° C., and a polymerization reaction (seed polymerization) was performed for 5 hours.

[0281] Next, steam is introduced to remove unreacted monomers and initiator decomposition products, thereby obtaining an aqueous dispersion of organic particles.

[0282] (Example 9)

[0283] The functional layer composition prepared as follows was used, and except for preparing a water-soluble polymer, organic particles, a binder, a functional layer composition, a separator, a negative electrode, a positive electrode, and a secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0284] <Preparation of Composition for Functional Layer>

[0285] 70 parts (in terms of solid content) of the above organic particles, 30 parts of alumina particles (manufactured by Sumitomo Chemical Co., Ltd., product name "AKP-30") as inorganic particles, and 5 parts (in terms of solid content) of the above water-soluble polymer were mixed in a stirring container, and 10 parts (in terms of solid content) of the above binder were further added and mixed. Ion exchange water was added to the obtained mixed solution to prepare a composition for a functional layer (solid content concentration: 10%).

[0286] (Example 10)

[0287] <Preparation of organic particles, water-soluble polymer, binder, and functional layer composition>

[0288] Organic particles, a binder, and a composition for a functional layer were prepared in the same manner as in Example 1. Then, various evaluations were performed according to the above-mentioned methods. The results are shown in Table 2.

[0289] <Preparation of spacers>

[0290] A polyethylene spacer (manufactured by Asahi Kasei Corporation, product name "MD412") was prepared.

[0291] <Fabrication of Negative Electrode Having Functional Layer>

[0292] A negative electrode binder and a negative electrode slurry composition were prepared in the same manner as in Example 1. The negative electrode slurry composition was applied to a copper foil with a thickness of 20 μm as a current collector using a notch wheel coater so that the film thickness after drying was about 150 μm, and dried. The drying was carried out by conveying the copper foil in an oven at 60°C for 2 minutes at a speed of 0.5 m / min. Then, the negative electrode raw material before pressing was obtained by heating at 120°C for 2 minutes. The negative electrode raw material before pressing was rolled using a roller press to obtain a negative electrode substrate having a thickness of 80 μm for the negative electrode composite material layer.

[0293] The functional layer composition obtained above was applied onto the negative electrode composite material layer side of the negative electrode substrate, and the functional layer composition on the negative electrode substrate was dried at 50° C. for 3 minutes to form a functional layer (thickness: 0.5 μm), thereby obtaining a negative electrode having a functional layer.

[0294] <Production of positive electrode>

[0295] In the same manner as in Example 1, a positive electrode was produced.

[0296] <Manufacturing of Secondary Battery>

[0297] The pressed positive electrode obtained by the above is cut into 49cm×5cm and placed on the table with the surface on the positive electrode composite material layer facing up. Then, a separator cut into 120cm×5.5cm is arranged on the positive electrode composite material layer of the positive electrode. Furthermore, the negative electrode obtained by the above is cut into 50cm×5.2cm, and the negative electrode is arranged on the above separator in a manner that the surface on the functional layer side is opposite to the separator, thereby obtaining a laminate. The laminate is wound using a winding machine to obtain a wound body. Furthermore, the wound body is pressed at 60°C and 0.5MPa to form a flat body. Then, the flat body is wrapped with an aluminum packaging material outer packaging as the outer packaging of the battery, and the electrolyte (solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate (volume mixing ratio) = 68.5 / 30 / 1.5, electrolyte: LiPF6 with a concentration of 1M) is injected in a manner to exhaust the air. Next, in order to seal the opening of the aluminum package, the opening of the aluminum outer package was sealed by heat sealing at 150°C, and the wound body and the aluminum outer package were pressed at 60°C and 0.5 MPa to produce a 1000 mAh wound lithium ion secondary battery. The cycle characteristics of the obtained lithium ion secondary battery were evaluated. The results are shown in Table 2.

[0298] (Example 11)

[0299] When preparing organic particles, except that trimethylolpropane-trimethacrylate was used instead of ethylene glycol dimethacrylate, organic particles, a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were produced in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0300] (Comparative Example 1)

[0301] Organic particles, a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were produced in the same manner as in Example 1 except that the water-soluble polymer prepared as described below was used. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0302] <Preparation of water-soluble polymer>

[0303] In a four-necked flask with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 1 part of dimethylacrylamide as a (meth)acrylamide monomer and 90 parts of acrylamide, 9 parts of methacrylic acid as an acidic group-containing monomer, 365 parts of ion exchange water and 5 parts of isopropanol were added, and nitrogen was used to remove oxygen in the reaction system. Next, under stirring, 7 parts of a 5% aqueous solution of ammonium persulfate and 3 parts of a 5% aqueous solution of sodium bisulfite were added to the flask as a polymerization initiator, and the temperature was raised from room temperature to 80°C and kept warm for 3 hours. Then, 162 parts of ion exchange water were added, and the pH was adjusted to 5 using 48% sodium hydroxide. Further ion exchange water was added to obtain an aqueous solution of a water-soluble polymer (solid content concentration: 5%).

[0304] (Comparative Examples 2 to 3)

[0305] Instead of polyvinyl alcohol (KURARAY CO., LTD., product name "PVA110"), sodium polyacrylate (TOAGOSEI CO., LTD., product name "Aron A-30") (Comparative Example 2), imidized isobutyl maleic acid copolymer (KURARAY CO., LTD., product name "ISOBAM304") (Comparative Example 3) were used as water-soluble polymers. Organic particles, binding materials, functional layer compositions, separators, negative electrodes, positive electrodes, and secondary batteries were manufactured in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0306] (Comparative Example 4)

[0307] The water-soluble polymer was prepared in the same manner as in Example 1, and a binder, a composition for a functional layer, a separator, a negative electrode, a positive electrode, and a secondary battery were manufactured in the same manner as in Example 1, except that the organic particles prepared as follows were used. Then, various evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0308] <Preparation of organic particles>

[0309] In a reactor A having a stirrer, 0.05 parts of sodium dodecylbenzene sulfonate, 0.3 parts of ammonium persulfate and 100 parts of ion exchange water are added and mixed to form a mixture, and the temperature is raised to 80°C. On the other hand, 5 parts of ethylene glycol dimethacrylate (KYOEISHA CHEMICAL Co., LTD., product name "Light Ester EG") as a multifunctional monomer, 93 parts of methyl methacrylate as a monofunctional (meth) acrylate monomer, 2 parts of acrylic acid as an acidic group-containing monomer, 0.5 parts of sodium dodecylbenzene sulfonate and 100 parts of ion exchange water are mixed in another container to prepare a monomer composition. The monomer composition is continuously added to the polymer obtained above for 4 hours and polymerized. When the monomer composition is continuously added, the temperature of the reaction system is maintained at 80°C and the reaction is carried out. After the continuous addition is completed, the reaction is further continued at 90°C for 3 hours to obtain an aqueous dispersion of organic particles.

[0310] In addition, in Table 1 and Table 2 shown below,

[0311] "EDMA" means ethylene glycol dimethacrylate units,

[0312] "TMPTMA" means trihydroxypropane-trimethacrylate units,

[0313] "BA" refers to n-butyl acrylate units,

[0314] "MMA" means methyl methacrylate units,

[0315] "AA" represents acrylic acid unit,

[0316] "VAL" means vinyl alcohol unit,

[0317] "HEAAm" means 2-hydroxyethylacrylamide,

[0318] "VAc" represents vinyl acetate units,

[0319] "AAm" represents acrylamide unit,

[0320] "DMAA" means dimethylacrylamide unit,

[0321] "SPA" stands for sodium polyacrylate.

[0322] "IIM" means imidized isobutyl maleic acid copolymer,

[0323] "ACL" means acrylic acid polymer.

[0324] [Table 1]

[0325]

[0326] [Table 2]

[0327]

[0328] As shown in Tables 1 and 2, in Examples 1 to 11, a functional layer composition containing organic particles and a water-soluble polymer in water is used, wherein the organic particles contain a multifunctional monomer unit at a ratio of 20% by mass or more and 95% by mass or less, and the water-soluble polymer contains a hydroxyl-containing structural unit at a ratio of 15% by mass or more and 100% by mass or less. In such Examples 1 to 11, the slurry stability of the functional layer composition is excellent, and if the functional layer composition is used, a functional layer with excellent heat shrinkage resistance can be formed. Moreover, in Examples 1 to 11, the coating stability of the functional layer composition can be ensured, the amount of water brought into the secondary battery can be reduced, and the secondary battery can be made to exhibit good cycle characteristics.

[0329] On the other hand, in Comparative Examples 1 to 3, a functional layer composition containing a water-soluble polymer having a hydroxyl-containing structural unit content of less than 15% by mass was used. In such Comparative Examples 1 to 3, the slurry stability of the functional layer composition was reduced.

[0330] Furthermore, in Comparative Example 4, a composition for a functional layer containing organic particles was used, and the content ratio of the polyfunctional monomer unit of the organic particles was less than 20% by mass. In such Comparative Example 4, the heat shrinkage resistance of the functional layer was reduced.

[0331] Industrial Applicability

[0332] According to the present invention, it is possible to provide a composition for a non-aqueous secondary battery functional layer which is excellent in slurry stability and can form a functional layer having sufficiently ensured heat shrinkage resistance.

[0333] Furthermore, according to the present invention, it is possible to provide a nonaqueous secondary battery functional layer having excellent heat shrinkage resistance, a nonaqueous secondary battery member having the functional layer, and a nonaqueous secondary battery having the battery member.

Claims

1. A composition for a non-aqueous secondary battery functional layer, comprising organic particles, a water-soluble polymer and water, The organic particles contain a polyfunctional (meth)acrylate monomer unit in a ratio of 50 mass % or more and 95 mass % or less, The water-soluble polymer is nonionic and contains a hydroxyl group-containing structural unit in a ratio of 15% by mass or more and 100% by mass or less. The organic particles have a glass transition temperature of 100° C. or higher and a volume average particle size of 50 nm or more and 500 nm or less, The weight average molecular weight of the water-soluble polymer is greater than or equal to 30,000 and less than 50,000. The saponification degree of the water-soluble polymer is 90 mol% or more and 100 mol% or less, The amount of the water-soluble polymer blended is 0.1 parts by mass or more and 15 parts by mass or less relative to 100 parts by mass of the organic particles. 2 . A non-aqueous secondary battery functional layer formed using the composition for a non-aqueous secondary battery functional layer according to claim 1 . 3 . A non-aqueous secondary battery member comprising the non-aqueous secondary battery functional layer according to claim 2 . 4 . A non-aqueous secondary battery comprising the non-aqueous secondary battery component according to claim 3 .